Aprimoramento de biossensor de lacase para determinação de micropoluentes fenólicos em águas contaminadas - Ribeiro Júnior, Eli José Miranda (2015)
Laccase is a poliphenoloxidase enzyme that catalyzes the oxidation of phenolic compounds in the corresponding quinones. The current obtained in this redox process can be used for quantitative analysis. In this work, a carbon paste biosensor modified gluteraldehyde functionalized silica and an enzymatic extract of the “Pycnoporus sanguineus” fungi as a lacase source is proposed for phenol determination. The effect of carbon paste and electrolyte composition, pH from 3,0 to 8,0, start potential from 0,55 to 0,25mV, scan rate from 5 to 25 mV s-1 and potential pulse amplitude from 10 to 60mV on the differential pulse voltammetric response was investigated. A linear correlation of R² = 0,9946 was obtained for the phenol content (catechol) in the concentration range from 50 to 500nMol L-1, with a detection limit of 30nMol L-1. This biosensor was used for the determination of different kinds of phenolic compounds, presenting a better response for catechol.